A Cartographic Analysis of the Syntactic Structure of Mandarin Ba - Sun Yangyu (Sciendo, 2018)
This paper analyzes the syntactic properties of the “ba-construction” or “disposal form” in Mandarin Chinese under new theoretical frameworks. By introducing the event-decomposition method proposed by Ramchand (2008), it argues that the ba-construction conveys the causativity and the resultativity of the event at the same time, which can be shown from the syntactic representation. Then, this paper tests the position of ba, assuming that it is a functional head, and the result of the test indicates that ba is a voice head in the hierarchy of functional projections proposed by Cinque (1999, 2006). The final word order of a ba-construction can be derived by the argument movement of the direct object and by a head movement of ba or by the merge of ba at the head position of the higher functional head of a split VoiceP.